2017
DOI: 10.1177/1687814017696227
|View full text |Cite
|
Sign up to set email alerts
|

Pressure fluctuation and flow pattern of a mixed-flow pump with different blade tip clearances under cavitation condition

Abstract: Cavitation phenomenon has strong transient characteristics and is highly influenced by geometric structure. In this study, the cavitation performance with influence of blade tip clearance for a mixed-flow pump is studied using the renormalization group (RNG) k-e turbulence model and the Zwart-Gerber-Belamri cavitation model. The dominant frequency and maximum amplitude values at non-cavitation condition and different cavitation conditions are compared and associated with flow field features. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 12 publications
(12 reference statements)
0
29
0
Order By: Relevance
“…3 In contrast, the cloud cavity is eventually separated at the impeller shroud along the streamwise direction. [4][5][6][7] The cloud cavity is complex owing to the flow rates and blade geometries. [8][9][10] Among the two representative classes of the cavity, this study is focused on the former, sheet cavity.…”
Section: Introductionmentioning
confidence: 99%
“…3 In contrast, the cloud cavity is eventually separated at the impeller shroud along the streamwise direction. [4][5][6][7] The cloud cavity is complex owing to the flow rates and blade geometries. [8][9][10] Among the two representative classes of the cavity, this study is focused on the former, sheet cavity.…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the shortage of experimental methods, computational fluid dynamics (CFD) methods were used, and its predictions of cavitation behaviors in centrifugal pumps revealed interesting results. During the simulation, the Reynolds-averaged Navier-Stokes (RANS) equations coupled with a homogeneous mixture of cavitation models were applied to obtain a clearer picture of transient cavitation flow structures and pressure pulsations in both the rotating part (impeller) and stationary part (volute or vane diffusor) [7][8][9][10][11]. In addition, a number of studies focused primarily on the structural behaviors of pumps under cavitation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation also influences the characteristics of pressure fluctuations. Xu [73] found that the maximum magnitude of pressure fluctuation increases with the deteriorating cavitation induced by increasing the tip clearance in a mixed-flow pump. characteristics of pressure fluctuations.…”
Section: Pressure Fluctuationmentioning
confidence: 99%
“…characteristics of pressure fluctuations. Xu [73] found that the maximum magnitude of pressure fluctuation increases with the deteriorating cavitation induced by increasing the tip clearance in a mixed-flow pump. The above analyses illustrate that the influence of tip clearance on pressure fluctuation has various forms in terms of magnitude, frequency, and variation trends for different types of pumps and turbines, and the variation of the impact is due to the complex flow pattern in those divers machineries.…”
Section: Pressure Fluctuationmentioning
confidence: 99%
See 1 more Smart Citation